Pengujian Mesin Pendingin Minuman Portable Menggunakan Port USB Dan Adaptor Sebagai Daya Input - Syukrillah, Muhammad Faizal; Mainil, Rahmat Iman; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Thermoelectric is one of the cooling technology alternatives other than vapor compression systems. Thermoelectric is used as a cooling media in a portable beverage cooler. This study aims to measure temperature of portable beverage cooler using thermoelectric module with cooling load and without cooling load. The temperature observed were hot side temperature (heatsink), cold side temperature (the inner wall), cooling chamber temperature, ambient temperature, outside wall temperature and water temperature. Experiments had been carried out using an adapter and USB as primary power for 30 minutes. The results reveal that the use of an adapter in the voltage of 12 V provides better cooling. This could be seen after 30 minutes the lowest temperature cooling chamber without cooling load is 9,7 °C, with a cooling load beverage cans of 250 ml is 18,7 °C, with acooling load milk box of 250 ml is 18,4 ° C, and with a cooling load isotonic drink of 140 ml is 14,8 °C.Keywords : Thermoelectric, Portable Beverage Cooler, Peltier Effect, Cooling Load